Efek Pemberian Air Kelapa dan Air Alkalin pada Kadar Asam Laktat Pasca Aktivitas Fisik Intensitas Tinggi: The Effect of Coconut Water and Alkaline Water Intake on Lactic Acid Levels After High Intensity Physical Activity - Sofi, Moh Sofyan; Pribadi, Heri Purnama; Fitria, Anisa Lailatul (Universitas Airlangga, 2026)
Background: Lactic acid is a primary biomarker of fatigue, produced as a byproduct of anaerobic energy metabolism. Elevated lactic acid levels are associated with muscle fatigue and reduced performance. Consuming alkaline drinks can help speed up the reduction of lactic acid levels. Coconut water, which is rich in nutrients and electrolytes, can also be an alternative for recovery after intense physical activity. Objectives: Evaluate the effect of coconut water and alkaline water on lactic acid after high-intensity physical activity. Methods: Study participants were male university students divided into two groups: alkaline water group (K1) and coconut water group (K2), each consisting of 13 participants with similar characteristics. K1 was given 350 ml of alkaline water and K2 was given 350 ml of coconut water. Lactic acid levels were measured before and after performing a 35-meter sprint running six times. Differences in lactic acid levels between groups were analyzed using an independent t-test. Results: Pre-activity lactic acid levels were 2.55 ± 0.54 mmol/L for the K1 group and 3.2 ± 0.53 mmol/L for the K2 group. Post-intervention, the levels rose to 6.63 ± 2.54 mmol/L for K1 and 8.3 ± 3.15 mmol/L for K2. There was no statistically significant difference in the increase of lactic acid levels between groups (p-value=0.414). Non-significant results indicate that both liquids have an influence on changes in lactic acid levels. Conclusions: Both alkaline water and coconut water demonstrated similar effects in inhibiting the accumulation of lactic acid following high-intensity physical activity.